Lack of Adipocyte-Fndc5/Irisin Expression and Secretion Reduces Thermogenesis and Enhances Adipogenesis. Issue 1 (December 2017) - Pérez-Sotelo, D.; Roca-Rivada, A.; Baamonde, I.; Baltar, J.; Castro, A.; Domínguez, E.; Collado, M.; Casanueva, F.; Pardo, M.
Abstract Irisin is a browning-stimulating molecule secreted from the fibronectin type III domain containing 5 precursor (FNDC5) by muscle tissue upon exercise stimulation. Despite its beneficial role, there is an unmet and clamorous need to discern many essential aspects of this protein and its mechanism of action not only as a myokine but also as an adipokine. Here we contribute to address this topic by revealing the nature and role of FNDC5/irisin in adipose tissue. First, we show that FNDC5/irisin expression and secretion are induced by adipocyte differentiation and confirm its over-secretion by human obese visceral (VAT) and subcutaneous (SAT) adipose tissues. Second, we show how secreted factors from human obese VAT and SAT decrease PGC1α, FNDC5 and UCP1 gene expression on differentiating adipocytes; this effect over UCP1 is blunted by blocking irisin in obese secretomes. Finally, by stable gene silencing FNDC5 we reveal that FNDC5-KO adipocytes show reduced UCP1 expression and enhanced adipogenesis.